Analisis Kuat Tekan dan Absorpsi Mortar untuk Pasangan Dinding Bata dengan Bahan Tambah Bubuk Cangkang Telur - Gian Fidela; Suhendra Suhendra; Wari Dony; Fadlan Fadlan (Universitas Batanghari Jambi, 2023)
The development of development in Indonesia is progressing rapidly and therefore it does not result in a negative impact on the environment, one of the ideas that can be done to solve this problem in terms of construction is by utilizing waste from egg shells. Waste Egg shell powder is produced from crushed dried chicken eggshell waste. The eggshell contains 97% calcium carbonate. The high calcium content in eggs has the potential to be used as an additive in the manufacture of cement. This study aims to determine the compressive strength and absorption of mortar by being a substitute for cement by 2.5% to 15%. The method of testing the compressive strength and absorption of mortar refers to SNI 03-6825-2002 and SNI 03-6433-2000. The amount of mortar is 42 cubes with a cube size of 5x5x5 cm3. Each variation has 21 mortar cubes for compressive strength and 21 mortar cubes for absorption. The range of flow values used is 105% -115%. The mortar specimens were soaked for 26 days and the test was carried out at 28 days of age. The greatest value of mortar compressive strength occurs in 2.5% eggshell powder of 11.64 MPa with a percentage increase in compressive strength of 20.37% from normal mortar. The greatest mortar absorption occurred in 7.5% eggshell powder by 15.03% and the smallest absorption occurred in the addition of 2.5% eggshell powder by 6.94%.